Diseño de un plan estratégico de mercadeo para la empresa centro eléctrico (2021)
In the present work, a strategic marketing plan was designed for the Centro Eléctrico company, with the aim of improving its profitability and increasing its market share, so that the company can have greater stability and control in its activities, for this, An investigation was carried out based on the analysis and interpretation of data inside and outside the company, as well as all the information concerning it was used. Taking into account the research carried out, a diagnosis and market study of the Electric Center was carried out, determining its weaknesses, opportunities, strengths and threats, analyzing the products it offers, the market, the processes used, human resources, competition, the needs of customers and the potential of the products offered by the company, to establish strategies that can improve its position in the market and global performance.